Management accounting : control and audit. Stage 4 - Chartered Institute of Management Accountants (London : BPP, 1990)
One of a series of regularly updated Study Texts providing coverage of the examinations of the Chartered Institute of Management Accountants (CIMA), this covers the entire syllabus and includes numerous questions from past examinations with full suggested solutions
Keywords: Managerial accounting